Evolving Roles and Needs of Psychiatry Chief Residents During the COVID-19 Pandemic and Beyond - Ratnakaran B; Hanafi S; Wobbe H; Howland M (Dove Medical Press, 2023)
Badr Ratnakaran,1 Sarah Hanafi,2 Heather Wobbe,3 Molly Howland4 1Department of Psychiatry, Carilion Clinic-Virginia Tech Carilion School of Medicine, Roanoke, VA, USA; 2Department of Psychiatry, McGill University, Montreal, QC, Canada; 3Department of Psychiatry, Summa Health, Akron, OH, USA; 4Department of Psychiatry, Cleveland Clinic, Cleveland, OH, USACorrespondence: Badr Ratnakaran, Department of Psychiatry, Carilion Clinic-Virginia Tech Carilion School of Medicine, 2017, S Jefferson St, Roanoke, VA, USA, Tel +1 540-855-4648, Fax +1 540 981-7653, Email dr.badrratnakaran@gmail.comAbstract: Psychiatry chief residents have diverse leadership roles within psychiatry residency programs. Chief residents have historically been viewed as "middle managers", and other leadership roles include administrative work, teaching, and advocacy for residents. Chief residents also help in managing the logistics of complex healthcare systems and mediating between many groups with conflicting needs and perspectives. The COVID-19 pandemic has changed the functioning of psychiatry residency programs, and this has also led to the evolution of the roles of the chief residents in psychiatry. During the COVID-19 pandemic, the chief residents had to help with adapting to the changes in teaching and clinical work with residents and faculty. They had to liaison with various healthcare providers in making decisions related to COVID-19 in residency programs. Along with these changes, chief residents also had to advocate for the wellbeing and needs of their fellow residents. This perspective article is written by authors who have served during or after the transition to the COVID-19 pandemic. We discuss our experiences as chief residents as well as evolving roles and wellness needs of chief residents in psychiatry. Based on the administrative, advocacy, academic and middle management roles of chief residents in psychiatry and their wellbeing, we also make recommendations for support and interventions needed for chief residents in the context of the COVID-19 pandemic and beyond.Keywords: chief residents, psychiatry, COVID-19